2009
DOI: 10.2337/dc09-1302
|View full text |Cite
|
Sign up to set email alerts
|

Emphasis on Carbohydrates May Negatively Influence Dietary Patterns in Youth With Type 1 Diabetes

Abstract: OBJECTIVETo assess perceptions of healthful eating and the influence of diabetes management on dietary behaviors among youth with type 1 diabetes and parents.RESEARCH DESIGN AND METHODSYouth with type 1 diabetes (n = 35), ages 8–21 years, and parents participated in focus groups. Focus group recordings were transcribed and coded into themes. Clinical data were abstracted from the electronic medical record.RESULTSCentral topics were perceptions of healthful eating and the impact of diabetes management on diet. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(72 citation statements)
references
References 13 publications
2
68
0
2
Order By: Relevance
“…1 Although dietary intake is an integral part of diabetes management, 35 previous research suggests that families of youth with T1D may not prioritize healthful eating, given the multiple demands of diabetes management, as well as barriers to healthy eating such as the widespread availability of unhealthy foods, lack of food preparation time and desire for intakes consistent with friends given the already substantial differences placed upon the youth with diabetes compared with their peer group. 19,36 In addition, some families may focus on a food’s postprandial glycemic response, emphasizing both the amount of carbohydrate and ease of carbohydrate estimation, which may limit the foods children with T1D choose to eat. 36 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Although dietary intake is an integral part of diabetes management, 35 previous research suggests that families of youth with T1D may not prioritize healthful eating, given the multiple demands of diabetes management, as well as barriers to healthy eating such as the widespread availability of unhealthy foods, lack of food preparation time and desire for intakes consistent with friends given the already substantial differences placed upon the youth with diabetes compared with their peer group. 19,36 In addition, some families may focus on a food’s postprandial glycemic response, emphasizing both the amount of carbohydrate and ease of carbohydrate estimation, which may limit the foods children with T1D choose to eat. 36 …”
Section: Discussionmentioning
confidence: 99%
“…19,36 In addition, some families may focus on a food’s postprandial glycemic response, emphasizing both the amount of carbohydrate and ease of carbohydrate estimation, which may limit the foods children with T1D choose to eat. 36 …”
Section: Discussionmentioning
confidence: 99%
“…330 However, reduction of carbohydrate may contribute to increased fat intake as diabetes mellitus management (to improve glucose control) and may have negative effects on cardiovascular health. 331,332 Youth with T1DM have documented higher fat intakes that are positively associated with HbA 1c levels. 333 Disturbed eating behaviors are common among youth with T1DM.…”
Section: Type 1 Diabetes Mellitusmentioning
confidence: 99%
“…It has been postulated that an increased focus on carbohydrate counting can lead to an increased intake of packaged food as the nutrition label facilitates carbohydrate counting. There is evidence to suggest that people with type 1 diabetes consume excess protein and fat and are at increased risk of cardiovascular disease (Mehta, Haynie, Higgins, & Laffel, 2009;Overby, King, et al, 2006). It is therefore imperative that healthy eating remains central in diabetes education, with an emphasis on selecting foods for their nutritional value rather than based on their ease of carbohydrate quantification.…”
Section: How Accurately Do People With Type 1 Diabetes Need To Count mentioning
confidence: 99%
“…Some participants reported that their fat consumption increased as carbohydrate free, high fat meals were perceived as the easy option . Given that people with type 1 diabetes reportedly have higher total fat and saturated fat intakes than healthy people (Overby et al, 2006;Helgeson, Viccaro, Becker, Escobar, & Siminerio, 2006) and their fruit, vegetable and fiber intakes fall below recommendations (Pietilainen, Virtanen, Rissanen, Rita, & Maenpaa, 1995;Nansel et al, 2012), care is needed when teaching carbohydrate counting that an emphasis on carbohydrate does not detract from healthy eating principles (Mehta, Haynie, et al, 2009).…”
Section: How Accurately Can People With Type 1 Diabetes Count Carbohymentioning
confidence: 99%